2015
DOI: 10.1002/ep.12157
|View full text |Cite
|
Sign up to set email alerts
|

Impact of density loads on performance of duckweed bioreactor: A potential system for synchronized wastewater treatment and energy biomass production

Abstract: Duckweed Lemna gibba has been listed as a promising plant for wastewater treatment and energy biomass production. This study aims to study the efficacy of L. gibba based bioreactor in removal of wastewater pollutants loads and energy-rich biomass harvesting under different plant biomass density loads. A total of four density loads: 20% (T1), 40% (T2), 60% (T3), and 80% (T4) of inoculants biomass were used to construct duckweed reactors and changes in wastewater (WW) and duckweed biomass characteristics (growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Fast growing duckweed in nutrient rich water is a highly efficient sink for both phosphorus and potassium; little of each, however, is required for rapid growth. In concurrence with the present findings, Verma and Suthar [13] have also reported that the nutrient load in wastewater reduced significantly by 83-89% of NO 3 -and 67-72% of total phosphorus. Pandey [14] reported that in the duckweed treatment system at Halisahar, nitrogen and phosphorus removals were in the range of 50-75% and 17-35% respectively.…”
Section: Macronutrients (N P K Ca Mg)supporting
confidence: 93%
“…Fast growing duckweed in nutrient rich water is a highly efficient sink for both phosphorus and potassium; little of each, however, is required for rapid growth. In concurrence with the present findings, Verma and Suthar [13] have also reported that the nutrient load in wastewater reduced significantly by 83-89% of NO 3 -and 67-72% of total phosphorus. Pandey [14] reported that in the duckweed treatment system at Halisahar, nitrogen and phosphorus removals were in the range of 50-75% and 17-35% respectively.…”
Section: Macronutrients (N P K Ca Mg)supporting
confidence: 93%
“…As such, the absolute biomass yield is an important parameter, as it relates directly to the amount of plant mass available for further use [ 27 ]. Previously, high duckweed densities of 60–80% plant coverage (around 160–280 g m −2 ) have been reported to result in maximum yields, in combination with different harvesting regimes [ 39 , 79 , 80 ]. Data from stationary experiment 1 and the re-circulating experiment show that at higher plant densities the logarithmic relationship between plant density and yield will plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Diluted (50%) SeSW was less stressful to L. punctata, which was reflected by higher rates of nutrient uptake: 74%, 43%, and 94% for NH 4 , PO 4 and NO 3 , respectively (Table 1, Figure 1). A broad spectrum of absorption rates of nutrients by L. punctata and other duckweed species has been reported [6,14,30,32,[34][35][36]58,[62][63][64][65][66][67][68]. Short-term treatment of the SeSW by L. punctata did not lead to a significant increase in biomass production (1.5-fold, Table 1).…”
Section: Removal Of Nitrogen and Phosphorus By L Punctatamentioning
confidence: 94%